2021
DOI: 10.3390/s21062029
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Performance of Multi-Frequency Low-Cost GNSS Receivers and Antennas

Abstract: Global Navigation Satellite System (GNSS) low-cost multi-frequency receivers are argued as an alternative to geodetic receivers for many applications. Calibrated low-cost antennas recently became available on the market making low-cost instruments more comparable with geodetic ones. The main goal of this research was to evaluate the noise of low-cost GNSS receivers, to compare the positioning quality from different types of low-cost antennas, and to analyze the positioning differences between low-cost and geod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 37 publications
(53 reference statements)
0
12
0
1
Order By: Relevance
“…In addition, it was noted that the main source of height error was the use of low-cost antennas. Further tests for this receiver were performed by Hamza et al [ 24 ], who used low-cost antennas from various manufacturers to determine position using the static method. Their results allowed them to conclude that low-cost instruments give a coordinate accuracy of a few millimeters, but their precision is four times worse than that of geodetic receivers (based on adjustment of the established geodetic network).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was noted that the main source of height error was the use of low-cost antennas. Further tests for this receiver were performed by Hamza et al [ 24 ], who used low-cost antennas from various manufacturers to determine position using the static method. Their results allowed them to conclude that low-cost instruments give a coordinate accuracy of a few millimeters, but their precision is four times worse than that of geodetic receivers (based on adjustment of the established geodetic network).…”
Section: Introductionmentioning
confidence: 99%
“…Position accuracy from manufacture is confirmed by testing this module [10]. Some studies also confirmed this claim in open space without multipath [11] [12].…”
Section: Methodsmentioning
confidence: 70%
“…Recently, the u-blox ZED-F9P performance was thoroughly evaluated by the University of Ljubljana in Slovenia [55] . The aim of this specific study was to evaluate the noise of low-cost GNSS receivers, compare the positioning quality from different low-cost antennas and to analyse the positioning differences between low-cost and geodetic receivers.…”
Section: Validation and Characterizationmentioning
confidence: 99%